Cross-aisle seismic performance of selective storage racks. (May 2020) - Maguire, James R.; Teh, Lip H.; Clifton, G. Charles; Tang, Z.H.; Lim, James B.P.
Abstract: A series of single-axis shaking table tests were conducted on three full-scale selective storage racks in the cross-aisle direction. The uplifting and rocking behaviour of the racks was examined under three baseplate types: ductile, heavy duty, and unanchored. Each rack was subjected to a sequence of ground motions of increasing intensity up to failure, with a total of 29 tests conducted. At 1.5 times the respective design level ground motions, the heavy duty baseplates caused a foundation failure while the unanchored rack failed by overturning. The rack with ductile baseplates survived all tests up to 2.3 times the design level. For a given ground motion, the unanchored rack upright always had the smallest peak axial load. However, the unanchored rack had much larger sways under the Northbridge and Kobe ground motions. The NZS 1170.5 equivalent static method design loading was found to be overly conservative for racks with ductile and heavy duty baseplates, of which the upright design axial forces were better predicted using the refined equivalent static method. Highlights: Presents 29 shaking table tests of rocking racks. Includes three baseplate types with very different responses. Includes a comprehensive set of 12 ground motions. Provides insights into the behaviour of unanchored racks during earthquakes. Points out the conservatism of the existing equivalent static force method.